THE TRANSLATION INTO FRENCH OF THE EXCERPT FROM “THE SEASONS” BY KRISTIJONAS DONELAITIS - LEONAVIČIENĖ, AURELIJA (Knygotyra, 2015)
Contemporary translation theory defines translation as interlinguistic and intercultural communication, whereas the text is viewed as a complex semantic whole, where the meaning expressed by words does not always coincide with the associations implied by the meanings. The new contemporary paradigm of translation studies focuses on the cultural associations implied by texts and the cultural aspect of translation. Contemporary translation studies, which are more and more inclined towards cultural studies, are developing into an interdisciplinary and hybrid science in the periphery of linguistics, literature, and sociology. The article analyses microstructural units of text, their cultural interpretation and translation strategies of the translation into French of the excerpt from “The Seasons“ written by K. Donelaitis. The material of the analysis is an excerpt from “The Autumn’s Riches“, which is a part of the poem “The Seasons“ written by K. Donelaitis, and its translation. This part of the poem was published in the journal “Poesie 92. Revue bimestrielle de la poesie d’aujourd’hui“ in 1992, in Paris. The excerpt was translated by Ugnė Karvelis who was a native French speaker. Discussion about microstructural units of text (diminutives, culturespecific items, vivid verbs) and results of their contextual translation is based on perceptions of various translation theorists (M. Lederer, J.-L. Cordonnier, H. Gerzymisch-Arbogast, I. Fleddermanno, Mudersbach K. and others) and representatives of phenomenological and hermeneutical philosophy (Gadamer, P. Ricoeur). The analysis was made using the methods of quantitative and contrastive analysis of translation.The results of the translation analysis show that the translator of the excerpt from Lithuanian classic work paid greater attention to the stylistic meanings than the specific cultural meanings of the text and tried to adapt the text to the modern French reader who has little information about the context of Lithuanian peasant life in the eighteenth century, in the age of Enlightenment. Frequent cases of Lithuanian cultural meanings’ neutralization using strategies of semantic distribution change, omission and cultural actualisation show that these translation strategies were chosen due to some circumstances. They were chosen because of versification of the work and translator’s aim to make the French language sound more natural and due to the preconceived approach to adapt the literature of the previous epoch to the modern reader. The translation of the excerpt from K. Donelaitis work balances between loyalty to the original meanings (such as vivid verbs) and freedom to neutralize or to adapt cultural meanings of the text (e.g. culture-specific items). The translation of the excerpt from the poetical work complicates the process of cultural transposition and sometimes does not properly associate a part with a whole. These reasons may influence solutions of the translation. However, according to dominant translation strategies of the analysed extract, one can assume that if the translator had decided to translate the whole poem “The Seasons“, she would probably have chosen the way of cultural adaptation.
Keywords: ...